Methionine-Homocysteine Pathway in African-American Prostate Cancer. Issue 2 (25th April 2019) - Gohlke, Jie H; Lloyd, Stacy M; Basu, Sumanta; Putluri, Vasanta; Vareed, Shaiju K; Rasaily, Uttam; Piyarathna, Danthasinghe Waduge Badrajee; Fuentes, Hunter; Rajendiran, Thekkelnaycke M; Dorsey, Tiffany H; Ambati, Chandrashekar R; Sonavane, Rajni; et al.
Abstract: African American (AA) men have a 60% higher incidence and two times greater risk of dying of prostate cancer (PCa) than European American men, yet there is limited insight into the molecular mechanisms driving this difference. To our knowledge, metabolic alterations, a cancer-associated hallmark, have not been reported in AA PCa, despite their importance in tumor biology. Therefore, we measured 190 metabolites across ancestry-verified AA PCa/benign adjacent tissue pairs (n = 33 each) and identified alterations in the methionine-homocysteine pathway utilizing two-sided statistical tests for all comparisons. Consistent with this finding, methionine and homocysteine were elevated in plasma from AA PCa patients using case-control (AA PCa vs AA control, methionine: P  = .0007 and homocysteine: P  < .0001), biopsy cohorts (AA biopsy positive vs AA biopsy negative, methionine: P  = .0002 and homocysteine: P  < .0001), and race assignments based on either self-report (AA PCa vs European American PCa, methionine: P  = .001, homocysteine: P  < .0001) or West African ancestry (upper tertile vs middle tertile, homocysteine: P  < .0001; upper tertile vs low tertile, homocysteine: P  = .002). These findings demonstrate reprogrammed metabolism in AA PCa patients and provide a potential biological basis for PCa disparities.